A method for preparing low-sulfur and low-calcium clinker using phosphogypsum
Through the combination of phosphogypsum with siliceous, iron-aluminum and carbonaceous materials and the two-step decomposition and oxidation and firing process, the problem of high sulfur and calcium content in phosphogypsum is solved, energy consumption is reduced, and the mechanics of low-calcium clinker are improved. The performance of phosphogypsum is realized efficient resource utilization and environmentally friendly application.
Patent Information
- Application Number
- CN202310264749.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-20
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-03-20
AI Technical Summary
In the industrial utilization of phosphogypsum, the prior art is difficult to effectively reduce the sulfur and calcium content, while increasing the energy consumption and production cost of clinker. In addition, the mechanical properties of low-calcium clinker are insufficient, making it difficult to resource utilization of phosphogypsum on a large scale.
By mixing phosphogypsum, siliceous raw materials, iron-aluminum correction materials and carbonaceous raw materials, preheating, predecomposing and oxidizing sintering, two-step decomposition and oxidizing sintering processes are adopted to reduce the predecomposition temperature and reduce energy consumption. Form high-carbonization activity and low-calcium clinker to avoid the influence of SO3 and improve the mechanical properties of clinker.
The preparation of low sulfur and low calcium clinker is achieved, with low energy consumption, excellent compressive strength and flexural strength, and can greatly absorb phosphogypsum, solve the problem of disposal of phosphogypsum, and provide environmentally friendly application materials.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic materials, and in particular to a method for preparing low-sulfur and low-calcium clinker by utilizing phosphogypsum. Background Art
[0002] As an industrial product, phosphoric acid plays a huge role in agriculture, chemical industry, food, medicine and other fields. The supply of phosphoric acid is related to the basic livelihood of our country. However, a large amount of industrial waste will be generated in the process of industrial wet preparation of phosphoric acid, mainly phosphogypsum. The main component of phosphogypsum is calcium sulfate dihydrate. Compared with natural gypsum and industrial gypsum, phosphogypsum contains a large amount of organic phosphorus, fluoride, silicon dioxide, organic matter and other substances. On the one hand, these substances make phosphogypsum itself seriously harmful to the environment. On the other hand, the performance of dihydrate gypsum in phosphogypsum is seriously affected, which ultimately makes the resource utilization of phosphogypsum a major problem. It is urgent to develop large-scale resource-based phosphogypsum and dispose of phosphogypsum on a large scale.
[0003] The resource utilization of phosphogypsum in the field of building materials is a reliable way to achieve large-scale disposal of phosphogypsum. At present, the use of phosphogypsum to prepare clinker faces many difficulties. When using phosphogypsum to prepare ordinary Portland cement clinker, a large amount of SO 3 and SO 2 , and SO 3 and SO 2 It will seriously affect tricalcium silicate (C 3 S) will eventually affect the hydration performance of the clinker. The use of phosphogypsum to prepare sulphoaluminate cement clinker has limited absorption capacity. 3 and SO 2 The influence on the formation of clinker mineral phase is often achieved by completely decomposing the raw material before entering the kiln. 4 This technical solution is often achieved by increasing the decomposition temperature, which will inevitably increase the overall energy consumption of clinker preparation, thereby greatly increasing the cost of oxidation burning. For example, patent CN 115108744A sets up a double decomposition furnace to completely decompose CaSO 4 , it is necessary to significantly transform the existing equipment. At the same time, the high temperature of the No. 2 oxidation furnace will significantly increase the decomposition energy consumption. Low-calcium clinker does not contain C 3S, and it can obtain higher mechanical properties after carbonization curing, which is an ideal environmentally friendly material that can consume phosphogypsum on a large scale. However, the production of this material is also faced with the limitation of the desulfurization rate of phosphogypsum. If the desulfurization rate is increased in the pre-decomposition stage, the same technology as the existing cement clinker production needs to be adopted, which will face high costs and high requirements. Reducing the decomposition rate will generate sulfur silicate minerals and reduce the content of carbonizable components, which will eventually affect the performance of low-calcium clinker. Therefore, it is urgent to develop a method for preparing low-sulfur and low-calcium clinker using phosphogypsum with low energy consumption and low-sulfur and low-calcium clinker having excellent mechanical properties. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing low-sulfur and low-calcium clinker using phosphogypsum. The method provided by the present invention requires a low decomposition temperature and low energy consumption, and the prepared low-sulfur and low-calcium clinker has excellent compressive strength and flexural strength.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing low-sulfur and low-calcium clinker by using phosphogypsum, comprising the following steps:
[0007] (1) mixing phosphogypsum, siliceous raw materials, iron-aluminum corrective materials and carbonaceous raw materials to obtain a mixed raw material;
[0008] (2) Preheating, pre-decomposing and oxidatively burning the mixed raw material obtained in step (1) in sequence to obtain low-sulfur and low-calcium clinker.
[0009] Preferably, in step (1), the siliceous raw materials include one or more of sandstone, shale, silica, desert sand, siliceous tailings and clay, the iron-aluminum corrective material includes one or more of bauxite, iron powder, steel slag and red mud, and the carbonaceous raw materials include one or more of coal powder, coke and biomass fuel.
[0010] Preferably, in step (1), when the calcium-silicon molar ratio of the mixed raw material is 1.0 to 1.8, the Al 2 O 3 and Fe 2 O 3 The total mass fraction of Al in the mixed raw meal is ≤6%. When the calcium-silicon molar ratio of the mixed raw meal is 1.8-2.6, the Al 2 O 3 and Fe 2 O 3 The total mass fraction of Al in the mixed raw meal is ≤10%. When the calcium-silicon molar ratio of the mixed raw meal is 2.6-3.0, the Al 2 O 3 and Fe 2 O 3The total mass fraction is 10% to 20%.
[0011] Preferably, the average particle size of the mixed raw material in step (1) is less than 300 μm.
[0012] Preferably, the preheating temperature in step (2) is ≥ 750°C.
[0013] Preferably, the pre-decomposition temperature in step (2) is 850-1000°C.
[0014] Preferably, the oxidation calcination temperature in step (2) is 1200-1400° C., and the oxidation calcination time is 0.5-2 h.
[0015] Preferably, the SO in the low-sulfur and low-calcium clinker in step (2) 3 Content ≤1wt%.
[0016] The present invention provides low-sulfur and low-calcium clinker prepared by the method described in the above technical solution.
[0017] Preferably, by mass percentage, the CS, C 3 S 2 and C 2 The total amount of S>50%.
[0018] The present invention provides a method for preparing low-sulfur and low-calcium clinker by using phosphogypsum, comprising the following steps:
[0019] (1) mixing phosphogypsum, siliceous raw materials, iron and aluminum corrected materials and carbonaceous raw materials to obtain a mixed raw material; (2) preheating, pre-decomposing and oxidatively firing the mixed raw material obtained in step (1) in sequence to obtain a low-sulfur and low-calcium clinker. The present invention utilizes the mineral phase of the high-carbonization active low-calcium clinker to form a material that is not easily affected by SO during the oxidative firing process. 3 The characteristics of CaSO 4 The decomposition is split into two steps for pre-decomposition and oxidation firing, which greatly reduces the temperature of the pre-decomposition process and the energy consumption of pre-decomposition; the processes involved in the preparation process can be carried out with existing equipment, and there is no need to set up an additional oxidation decomposition furnace. Only the atmosphere control related devices need to be installed. It is easy to implement in actual industrial production, and there is no need to significantly modify the existing cement industry equipment; the process flow is simple, and the preparation method can significantly absorb phosphogypsum and solve the problem of difficult disposal of phosphogypsum; the prepared high carbonization activity low calcium clinker has extremely high mechanical properties after carbonization curing for 24 hours, and is an environmentally friendly material with a wide range of application scenarios. The results of the embodiment show that the low sulfur and low calcium clinker provided by the present invention has a compressive strength of ≥51MPa and a flexural strength of ≥10MPa after carbonization curing for 2 hours, and a compressive strength of ≥79MPa and a flexural strength of ≥15MPa after carbonization curing for 24 hours. DETAILED DESCRIPTION
[0020] The present invention provides a method for preparing low-sulfur and low-calcium clinker by using phosphogypsum, comprising the following steps:
[0021] (1) mixing phosphogypsum, siliceous raw materials, iron-aluminum corrective materials and carbonaceous raw materials to obtain a mixed raw material;
[0022] (2) Preheating, pre-decomposing and oxidatively burning the mixed raw material obtained in step (1) in sequence to obtain low-sulfur and low-calcium clinker.
[0023] The invention obtains mixed raw material by mixing phosphogypsum, siliceous raw materials, iron-aluminum corrective materials and carbonaceous raw materials.
[0024] In the present invention, the phosphogypsum, siliceous raw materials, iron-aluminum corrected materials and carbonaceous raw materials are preferably pretreated separately before use. In the present invention, the pretreatment includes drying, crushing and grinding treatments performed in sequence. In the present invention, the drying temperature is preferably 100-105°C, more preferably 105°C; the moisture content of the dried product is preferably ≤5wt.%. In the present invention, the particle size of the product after the grinding treatment is preferably <1mm. The present invention can remove moisture and reduce the particle size of the raw materials by pretreating the raw materials, which is conducive to subsequent mixing with other raw materials.
[0025] In the present invention, the content of CaO in the phosphogypsum is preferably>30wt.%; the siliceous raw materials preferably include one or more of sandstone, shale, silica, desert sand, siliceous tailings and clay; the iron-aluminum corrective material preferably includes one or more of bauxite, iron powder, steel slag and red mud; the carbonaceous raw materials preferably include one or more of coal powder, coke and biomass fuel. The present invention does not specifically limit the specific sources of the siliceous raw materials, iron-aluminum corrective materials and carbonaceous raw materials, and commercial products well known to those skilled in the art can be used.
[0026] The present invention preferably further adds a calcium raw material; the calcium raw material preferably includes one or more of limestone, slaked lime and carbide slag, more preferably limestone or slaked lime; the content of CaO in the chemical composition of the calcium raw material after burnout at 950° C. is preferably >90wt.%. The present invention uses the calcium raw material as a supplementary raw material, the main purpose of which is to correct the calcium component of the phosphogypsum for easy batching.
[0027] In the present invention, when the calcium-silicon molar ratio of the mixed raw material is preferably 1.0 to 1.8, the Al in the mixed raw material 2 O 3 and Fe 2 O 3The total mass fraction of Al in the mixed raw material is preferably ≤6%; when the calcium-silicon molar ratio of the mixed raw material is 1.8-2.6, 2 O 3 and Fe 2 O 3 The total mass fraction of Al in the mixed raw material is preferably ≤10%; when the calcium-silicon molar ratio of the mixed raw material is 2.6-3.0, 2 O 3 and Fe 2 O 3 The total mass fraction of is preferably 10% to 20%. 2 O 3 and Fe 2 O 3 The content can ensure the formation of suitable mineral phases in the subsequent process, thereby improving the performance of the clinker.
[0028] In the present invention, the mixing method is preferably grinding. In the present invention, the average particle size of the mixed raw material is preferably <300 μm. The present invention has no special limitation on the specific operation of the grinding, as long as the particle size of the mixed raw material meets the requirements.
[0029] After obtaining the mixed raw material, the present invention sequentially preheats, pre-decomposes and oxidizes the mixed raw material to obtain low-sulfur and low-calcium clinker.
[0030] In the present invention, the preheating temperature is preferably ≥ 750° C. The present invention facilitates subsequent pre-decomposition treatment of the mixed raw material by preheating the mixed raw material.
[0031] In the present invention, the pre-decomposition temperature is preferably 850 to 1000°C, more preferably 900 to 950°C; the pre-decomposition is preferably carried out in a reducing atmosphere; the pre-decomposition atmosphere contains O 2 The volume fraction is preferably <3 vol%, and the volume fraction of CO is preferably >3 vol%; the atmosphere of the pre-decomposition is preferably controlled by adjusting the air volume and injecting coal powder. In the present invention, the pre-decomposition product contains CaSO 4 The content of CaSO in phosphogypsum is preferably less than 3wt.%. The present invention can control the pre-decomposition temperature and atmosphere to make a part of CaSO 4 Decomposes into CaO and SO 3 , thereby improving the quality of clinker, while the low decomposition temperature can reduce energy consumption.
[0032] In the present invention, the pre-decomposition is preferably carried out in a decomposition furnace. The present invention has no particular limitation on the specific model of the decomposition furnace, and commercial products well known to those skilled in the art can be used.
[0033] In the present invention, the temperature of the oxidation calcination is preferably 1200-1400°C, more preferably 1250-1350°C, and further preferably 1300°C; the time of the oxidation calcination is preferably 0.5-2h, and more preferably 1-1.5h. In the present invention, the atmosphere of the oxidation calcination is preferably an oxidizing atmosphere; the concentration of oxygen in the oxidizing atmosphere is preferably >5vol%. By controlling the parameters of the oxidation calcination, the present invention can further reduce the undecomposed CaSO 4 During the oxidation sintering process, C 5 S 2 $mineral phase, thereby further improving the performance of low-sulfur and low-calcium clinker.
[0034] In the present invention, the oxidation calcination is preferably carried out in a rotary kiln. The present invention has no particular limitation on the specific model of the rotary kiln, and commercial products well known to those skilled in the art can be used.
[0035] The present invention has no special limitation on the specific operation of the grinding, as long as the average particle size of the low-sulfur and low-calcium clinker meets the requirements. In the present invention, the average particle size of the low-sulfur and low-calcium clinker is less than 150 μm. The present invention can further improve the mechanical properties of the low-sulfur and low-calcium clinker by controlling the particle size of the low-sulfur and low-calcium clinker.
[0036] In the present invention, the SO 3 The content of is preferably ≤1wt%.
[0037] The present invention utilizes the mineral phase of the high carbonization activity low calcium clinker to form a material that is not easily affected by SO during the oxidation firing process. 3 The characteristics of CaSO 4 The decomposition is divided into two steps: pre-decomposition and oxidation firing, which greatly reduces the temperature of the pre-decomposition process and reduces the energy consumption of the pre-decomposition; the processes involved in the preparation process can be carried out with existing equipment, and there is no need to set up an additional oxidation decomposition furnace. Only the relevant atmosphere control devices need to be installed. It is relatively easy to implement in actual industrial production, and there is no need to significantly modify the existing cement industry equipment; the process flow is simple, and the preparation method can significantly absorb phosphogypsum and solve the problem of difficult disposal of phosphogypsum; the prepared high-carbonization active low-calcium clinker has extremely high mechanical properties after 24 hours of carbonization curing, and is an environmentally friendly material with a wide range of application scenarios.
[0038] The present invention provides low-sulfur and low-calcium clinker prepared by the method described in the above technical solution.
[0039] In the present invention, by mass percentage, CS, C 3 S 2 and C 2The total amount of S is greater than 50%. The present invention can make the low-sulfur and low-calcium clinker have excellent mechanical properties by controlling the chemical composition of the clinker.
[0040] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] Example 1
[0042] A method for preparing low-sulfur and low-calcium clinker using phosphogypsum, comprising the following steps:
[0043] (1) drying, crushing and grinding phosphogypsum, siliceous raw materials, iron-aluminum corrected materials and carbonaceous raw materials in sequence, and then mixing and grinding to obtain a mixed raw material; the drying temperature is 105° C.; the particle size of the product after the grinding treatment is less than 1 mm; the moisture content of the mixed raw material is ≤5wt.%; the siliceous raw material is siliceous tailings, the iron-aluminum corrected material is bauxite, and the carbonaceous raw material is coal powder; the mass ratio of phosphogypsum, siliceous raw materials, iron-aluminum corrected materials and carbonaceous raw materials is 79:18:4:9; the average particle size of the mixed raw material is less than 300 μm;
[0044] (2) preheating the mixed raw material obtained in step (1) to 750° C., first pre-decomposing in a decomposition furnace, then oxidizing and calcining in a rotary kiln, and finally grinding when cooled to below 55° C. to obtain low-sulfur and low-calcium clinker; the pre-decomposition temperature is 900° C.; the pre-decomposition atmosphere contains oxygen 2 The volume fraction is <2 vol%, and the volume fraction of CO is 6 vol%; the pre-decomposition product contains CaSO 4 The content is less than 3wt.%; the oxidation firing temperature is 1300°C, the oxidation firing time is 0.5h, the oxidation firing atmosphere is an oxidizing atmosphere, and the oxidizing atmosphere is O 2 The volume fraction is 10 vol%.
[0045] In Example 1, 1.35 tons of phosphogypsum can be consumed for every ton of clinker prepared.
[0046] The main chemical compositions of the different raw materials after pretreatment in Example 1 were analyzed by XRF testing, and the results are shown in Table 1:
[0047] Table 1 Main chemical composition of different raw materials (wt.%)
[0048] LOI CaO <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[SO 3 ]]> Phosphogypsum 3.285 37.550 4.921 0.556 0.543 48.812 Silica tailings 2.336 4.731 76.431 9.114 2.605 0.028 Iron and aluminum correction material 12.500 4.200 16.700 61.000 0.172 0.089
[0049] The chemical composition of the mixed raw material obtained in step (1) of Example 1 is shown in Table 2:
[0050] Table 2 Chemical composition of the mixed raw material obtained in Example 1 (wt.%)
[0051]
[0052]
[0053] The composition of the low-sulfur and low-calcium clinker prepared in Example 1 was analyzed by XRD full spectrum fitting quantitative analysis, wherein C 2 S is β-C 2 S, γ-C 2 S, α-C 2 S and other different crystal forms C 2 The sum of S, SO 3 The f-CaO was determined by X-ray fluorescence detection according to the Chemical Analysis Methods for Cement (GB / T 176-2017). The results are shown in Table 3:
[0054] Table 3 Composition of low-sulfur and low-calcium clinker prepared in Example 1 (wt.%)
[0055]
[0056] Application Example 1
[0057] The low-sulfur and low-calcium clinker prepared in Example 1 and water were mixed at a mixing ratio of 0.15 and then carbonized and cured to obtain a sample. The compressive strength and flexural strength of the sample were tested. The size of the compressive strength sample was a cylinder of Φ20mm*20mm, and the size of the flexural strength sample was a cuboid of 37.5*6.5*6.8mm. The carbonization curing atmosphere was: 99% CO 2 , air pressure 0.3MPa, curing temperature is room temperature; strength test loading rate 200N / s, test results are shown in Table 4:
[0058] Table 4 Physical properties of low sulfur and low calcium clinker
[0059]
[0060] Example 2
[0061] A method for preparing low-sulfur and low-calcium clinker using phosphogypsum, comprising the following steps:
[0062] (1) drying, crushing and grinding phosphogypsum, siliceous raw materials, iron-aluminum corrected materials and carbonaceous raw materials in turn, and then mixing and grinding to obtain a mixed raw material; the drying temperature is 105°C; the particle size of the product after the grinding treatment is less than 1mm; the moisture content of the mixed raw material is ≤5wt.%; the siliceous raw material is siliceous tailings, the iron-aluminum corrected material is bauxite, and the carbonaceous raw material is coal powder; the mass ratio of phosphogypsum, siliceous raw materials, iron-aluminum corrected materials and carbonaceous raw materials is 77.8:21:1.2:9; the average particle size of the mixed raw material is less than 300μm;
[0063] (2) preheating the mixed raw material obtained in step (1) to 750° C., first pre-decomposing in a decomposition furnace, then oxidizing and calcining in a rotary kiln, and finally grinding when cooled to below 55° C. to obtain low-sulfur and low-calcium clinker; the pre-decomposition temperature is 900° C.; the pre-decomposition atmosphere contains oxygen 2 The volume fraction is <2 vol%, and the volume fraction of CO is 6 vol%; the pre-decomposition product contains CaSO 4 The content is less than 3wt.%; the oxidation firing temperature is 1300°C, the oxidation firing time is 0.5h, the oxidation firing atmosphere is an oxidizing atmosphere, and the oxidizing atmosphere is O 2 The volume fraction is 10 vol%.
[0064] In Example 2, 1.34 tons of phosphogypsum can be consumed for every ton of clinker prepared.
[0065] The main chemical compositions of the different raw materials after pretreatment in Example 2 were analyzed by XRF testing, and the results are shown in Table 5:
[0066] Table 5 Main chemical composition of different raw materials (wt.%)
[0067] LOI CaO <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[SO 3 ]]> Phosphogypsum 3.285 37.550 4.921 0.556 0.543 48.812 Silica tailings 1.650 1.041 88.772 5.393 1.166 0.070 Iron and aluminum correction material 12.500 4.200 16.700 61.000 0.172 0.089
[0068] The chemical composition of the mixed raw material obtained in step (1) of Example 2 is shown in Table 6:
[0069] Table 6 Chemical composition of the mixed raw material obtained in Example 2 (wt.%)
[0070] LOI CaO <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[SO 3 ]]> Mixed raw materials 3.048 29.474 22.714 2.278 0.668 37.981
[0071] The composition of the low-sulfur and low-calcium clinker prepared in Example 1 was analyzed by XRD full spectrum fitting quantitative analysis, wherein C 2 S is β-C 2 S, γ-C 2 S, α-C 2 S and other different crystal forms C 2 The sum of S, SO 3The f-CaO was determined by X-ray fluorescence detection according to the Chemical Analysis Methods for Cement (GB / T 176-2017). The results are shown in Table 7:
[0072] Table 7 Composition of low-sulfur and low-calcium clinker prepared in Example 2 (wt.%)
[0073]
[0074] Application Example 2
[0075] The low-sulfur and low-calcium clinker prepared in Example 2 and water were mixed at a mixing ratio of 0.15 and then carbonized and cured to obtain a sample. The compressive strength and flexural strength of the sample were tested. The size of the compressive strength sample was a cylinder of Φ20mm*20mm, and the size of the flexural strength sample was a cuboid of 37.5*6.5*6.8mm. The carbonization curing atmosphere was: 99% CO 2 , air pressure 0.3MPa, curing temperature is room temperature; strength test loading rate 200N / s, test results are shown in Table 8:
[0076] Table 8 Physical properties of low sulfur and low calcium clinker
[0077]
[0078] Example 3
[0079] A method for preparing low-sulfur and low-calcium clinker using phosphogypsum, comprising the following steps:
[0080] (1) drying, crushing and grinding phosphogypsum, calcium raw material, siliceous raw material, iron-aluminum correcting material and carbonaceous raw material in turn, and then mixing and grinding to obtain a mixed raw material; the drying temperature is 105°C; the particle size of the product after the grinding treatment is less than 1mm; the moisture content of the mixed raw material is ≤5wt.%; the siliceous raw material is siliceous tailings, the calcium raw material is limestone, the iron-aluminum correcting material is bauxite, and the carbonaceous raw material is coal powder; the mass ratio of the phosphogypsum, the siliceous raw material, the iron-aluminum correcting material and the carbonaceous raw material is 55.7:5.0:8.4:5.1:8.2; the average particle size of the mixed raw material is less than 300μm;
[0081] (2) preheating the mixed raw material obtained in step (1) to 750° C., first pre-decomposing in a decomposition furnace, then oxidizing and calcining in a rotary kiln, and finally grinding when cooled to below 55° C. to obtain low-sulfur and low-calcium clinker; the pre-decomposition temperature is 900° C.; the pre-decomposition atmosphere contains oxygen 2 The volume fraction is <2 vol%, and the volume fraction of CO is 6 vol%; the pre-decomposition product contains CaSO 4The content is less than 3wt.%; the oxidation firing temperature is 1300°C, the oxidation firing time is 0.5h, the oxidation firing atmosphere is an oxidizing atmosphere, and the oxidizing atmosphere is O 2 The volume fraction is 10 vol%.
[0082] In Example 3, 1.32 tons of phosphogypsum can be consumed for every ton of clinker prepared.
[0083] The main chemical compositions of the different raw materials after pretreatment in Example 3 were analyzed by XRF testing, and the results are shown in Table 9:
[0084] Table 9 Main chemical composition of different raw materials (wt.%)
[0085] LOI CaO <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[SO 3 ]]> Phosphogypsum 3.285 37.550 4.921 0.556 0.543 48.812 limestone 41.800 50.501 2.210 0.762 0.397 0.105 Silica tailings 2.336 4.731 76.431 9.114 2.605 0.028 Red Mud 10.001 2.468 13.241 27.559 40.192 0.673
[0086] The chemical composition of the mixed raw material obtained in step (1) of Example 3 is shown in Table 10:
[0087] Table 10 Chemical composition of the mixed raw material obtained in Example 3 (wt.%)
[0088] LOI CaO <![CDATA[SiO 2 ]]> <![CDATA[Al 2 THE 3 ]]> <![CDATA[Fe 2 THE 3 ]]> <![CDATA[SO 3 ]]> Mixed raw materials 6.235 32.296 13.406 3.395 3.492 36.698
[0089] The composition of the low-sulfur and low-calcium clinker prepared in Example 1 was analyzed by XRD full spectrum fitting quantitative analysis, wherein C 2 S is β-C 2 S, γ-C 2 S, α-C 2 S and other different crystal forms C 2 The sum of S, SO 3 The f-CaO was determined by X-ray fluorescence detection according to the Chemical Analysis Methods for Cement (GB / T 176-2017). The results are shown in Table 11:
[0090] Table 11 Composition of low-sulfur and low-calcium clinker prepared in Example 3 (wt.%)
[0091]
[0092]
[0093] Application Example 3
[0094] The low-sulfur and low-calcium clinker prepared in Example 3 and water were mixed at a mixing ratio of 0.15 and then carbonized and cured to obtain a sample. The compressive strength and flexural strength of the sample were tested. The size of the compressive strength sample was a cylinder of Φ20mm*20mm, and the size of the flexural strength sample was a cuboid of 37.5*6.5*6.8mm. The carbonization curing atmosphere was: 99% CO 2, air pressure 0.3MPa, curing temperature is room temperature; strength test loading rate 200N / s, test results are shown in Table 12:
[0095] Table 12 Physical properties of low sulfur and low calcium clinker
[0096]
[0097] It can be seen from Application Examples 1 to 3 that the sample obtained by the low-sulfur and low-calcium clinker prepared by the present invention has a compressive strength of ≥51MPa and a flexural strength of ≥10MPa after carbonization curing for 2h, and a compressive strength of ≥79MPa and a flexural strength of ≥15MPa after carbonization curing for 24h, and has excellent physical properties. At the same time, in the process of preparing low-sulfur and low-calcium clinker, one ton of low-sulfur and low-calcium clinker produced can consume more than 1.3 tons of phosphogypsum.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing low-sulfur and low-calcium clinker using phosphogypsum, comprising the following steps: (1) mixing phosphogypsum, siliceous raw materials, iron-aluminum corrective materials and carbonaceous raw materials to obtain a mixed raw material; (2) preheating, pre-decomposing and oxidatively burning the mixed raw material obtained in step (1) to obtain low-sulfur and low-calcium clinker; In the step (1), when the calcium-silicon molar ratio of the mixed raw meal is 1.0-1.8, the total mass fraction of Al2O3 and Fe2O3 in the mixed raw meal is ≤6%; when the calcium-silicon molar ratio of the mixed raw meal is 1.8-2.6, the total mass fraction of Al2O3 and Fe2O3 in the mixed raw meal is ≤10%; when the calcium-silicon molar ratio of the mixed raw meal is 2.6-3.0, the total mass fraction of Al2O3 and Fe2O3 in the mixed raw meal is 10%-20%; The preheating temperature in step (2) is ≥ 750°C; The pre-decomposition temperature in step (2) is 850-950°C; The oxidation calcination temperature in the step (2) is 1200-1300° C., and the oxidation calcination time is 0.5-2 hours.
2. The method according to claim 1, characterized in that In step (1), the siliceous raw materials include one or more of sandstone, shale, silica, desert sand, siliceous tailings and clay, the iron-aluminum corrective materials include one or more of bauxite, iron powder, steel slag and red mud, and the carbonaceous raw materials include one or more of coal powder, coke and biomass fuel.
3. The method according to claim 1, characterized in that The average particle size of the mixed raw material in step (1) is less than 300 μm.
4. The method according to claim 1, characterized in that The SO3 content in the low-sulfur and low-calcium clinker in step (2) is ≤1wt%.
5. Low-sulfur and low-calcium clinker prepared by the method according to any one of claims 1 to 4.
6. The low-sulfur and low-calcium clinker according to claim 5, characterized in that: Calculated by mass percentage, the total amount of CS, C3S2 and C2S in the low-sulfur and low-calcium clinker is greater than 50%.
Citation Information
Patent Citations
Method for preparing low-calcium self-pulverization clinker and co-producing sulfuric acid by utilizing phosphogypsum
CN114644466A